Transurethral Sphincterotomy and an Artificial Urinary Sphincter – A Novel 2-Stage Surgery for Refractory Bladder Emptying Disorders: A Proof-of-Concept Study - Kyung Tak Oh; Avelyn Noble Lim; Alwadai Raed Ibrahim; Jang Hwan Kim (International Neurourology Journal)
Purpose We developed an innovative 2-stage procedure combining transurethral sphincterotomy (TURS) with artificial urinary sphincter (AUS) implantation to restore voiding in patients with refractory bladder emptying disorders. This proof-of-concept study evaluated its safety and efficacy. Methods We retrospectively reviewed clinical data from patients who underwent combined TURS and AUS implantation between April 7, 2021, and October 31, 2024. Eligible patients had neurogenic bladder with refractory emptying, irreversible neurogenic disease, and no mechanical obstruction (e.g., urethral strictures). In the TURS stage, the entire inner urethral segment corresponding to the external sphincter was resected to induce intrinsic sphincter deficiency; this was followed by AUS placement. We analyzed patient demographics, preoperative and postoperative daily pad usage, clean intermittent catheterization (CIC) frequency, patient-reported outcomes (Life Quality [LQ], International Consultation on Incontinence Questionnaire [ICIQ], Sandvik Severity Index [SAND]), postvoid residual (PVR) urine volume, estimated glomerular filtration rate (eGFR), abdominopelvic ultrasonography, and postoperative complications. Results Four out of 6 patients (66.7%) successfully achieved CIC-free status, with effective self-voiding achieved through AUS activation and abdominal pressure generation. Significant improvements were documented in LQ scores (P=0.042), ICIQ scores (P=0.004), and SAND scores (P=0.039). Median PVR significantly decreased from 237.5 mL (interquartile range [IQR], 112.5–317.5 mL) preoperatively to 1.5 mL (IQR, 0–85.8 mL) postoperatively (P=0.028). No patient demonstrated upper-tract damage or significant eGFR change. One patient developed an AUS infection requiring explantation; another remained CIC-dependent due to insufficient abdominal pressure. Conclusions Combining TURS with AUS implantation is a safe and effective surgical option for refractory bladder emptying disorders, yielding significant improvements in voiding autonomy and quality of life while reducing catheter dependence. Future studies with larger cohorts and longer follow-up are warranted to validate safety, long-term durability, and broader applicability. These findings may shift current paradigms in neurogenic bladder management.